2015
DOI: 10.3996/102014-jfwm-074
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific Changes in Walleye Abundance, Size Structure and Harvest Following Implementation of Regulation to Protect Broodstock

Abstract: The popularity of walleye Sander vitreus fishing has resulted in the development of specialized regulations that are designed to protect these fisheries. In the case of Sherman Reservoir, Sherman County, Nebraska, the walleye population provides a sportfishing opportunity and serves as broodstock for the state. In 2009, for the primary purpose of protecting female broodstock, the regulation changed from a harvest limit of four walleye with 457-mm minimum length to allowing a reduced harvest limit of two walley… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Furthermore, the actual changes in exploitation that occurred in those studies were largely unknown, and in most cases, the sex-specific responses to changes in harvest regulations were not provided. Similar to our study, Koupal et al (2015) reported that allowing the harvest of two fish between 38.1 and 51.0 cm TL and one fish over 71 cm TL for Walleyes in Sherman Reservoir, Nebraska, increased the relative abundance of female Walleyes captured in spring netting, but the size structure of both sexes remained similar to that in previous years, when anglers could harvest four Walleyes of 45.7 cm TL and larger. Stone and Lott (2002) reported that a partial-year (April-June), 35.6-cm minimum length limit combined with a daily bag limit reduction from six fish to four fish and a possession limit reduction from 12 fish to 8 fish resulted in no changes in Walleye recruitment, growth, or abundance on Lake Francis Case, South Dakota, but did increase the PSD of quality-size (35.6-cm TL) Walleyes.…”
Section: Metricsupporting
confidence: 88%
“…Furthermore, the actual changes in exploitation that occurred in those studies were largely unknown, and in most cases, the sex-specific responses to changes in harvest regulations were not provided. Similar to our study, Koupal et al (2015) reported that allowing the harvest of two fish between 38.1 and 51.0 cm TL and one fish over 71 cm TL for Walleyes in Sherman Reservoir, Nebraska, increased the relative abundance of female Walleyes captured in spring netting, but the size structure of both sexes remained similar to that in previous years, when anglers could harvest four Walleyes of 45.7 cm TL and larger. Stone and Lott (2002) reported that a partial-year (April-June), 35.6-cm minimum length limit combined with a daily bag limit reduction from six fish to four fish and a possession limit reduction from 12 fish to 8 fish resulted in no changes in Walleye recruitment, growth, or abundance on Lake Francis Case, South Dakota, but did increase the PSD of quality-size (35.6-cm TL) Walleyes.…”
Section: Metricsupporting
confidence: 88%
“…The authors suggested that increased natural mortality of female Walleyes may have been the reason for the lack of gains in PSD-P. Similarly, following the enactment of a restrictive regulation on Sherman Reservoir, Nebraska, the size structure of the Walleye population remained the same, although the relative abundance of females that were collected as broodstock more than doubled (Koupal et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Examples include the establishment of a 711‐mm minimum length limit with one fish daily on Escanaba Lake, Wisconsin, in 2003 in an effort to increase the population size structure (Haglund et al 2016). At Sherman Reservoir, Nebraska, the daily bag limit for Walleyes was reduced from four fish with a 458‐mm minimum length limit to a two‐fish‐daily bag limit within a 381–508 mm harvestable slot and one fish >711 mm to protect Walleye broodstock (Koupal et al 2015).…”
mentioning
confidence: 99%
“…Greater protection of mature White Bass could be achieved via lowering the one over length threshold without substantially impacting the Hybrid Striped Bass population, but more research into harvest and the effects of various regulations is recommended before any new regulations would be implemented. Additionally, by managing two Moronid species with the same regulation, potential impacts of sex-specific mortality and harvest resulting from sexually-dimorphic growth differences (Koupal et al 2015) are likely to be mitigated, since the current regulation protects a small portion of adult White Bass but the majority of adult Hybrid Striped Bass. Faster female growth should result in earlier protection of females from both species and protect against any female-biased harvest (Schoenebeck and Brown 2011, Spirk 2012) and subsequent impacts to the fishery which may occur (Lauer et al 2008).…”
Section: Management Implicationsmentioning
confidence: 99%